Wyn Grant, William Paterson og Colin Whitston, Government and the Chemical Industry, A Comparative Study of Britain and West Germany, Oxford: Clarendon Press, 1988, 341 s., £ 35.00. - Ronit, Karsten (Politica, 1989)
-